2015
DOI: 10.1152/ajplung.00165.2015
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of pulmonary endothelial cyclic nucleotide response toPseudomonas aeruginosaExoY infection

Abstract: Morrow KA, Seifert R, Kaever V, Britain AL, Sayner SL, Ochoa CD, Cioffi EA, Frank DW, Rich TC, Stevens T. Heterogeneity of pulmonary endothelial cyclic nucleotide response to Pseudomonas aeruginosa ExoY infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 61 publications
(77 reference statements)
3
25
0
Order By: Relevance
“…2A). Endothelial cell gaps visible by light microscopy were first noted after 3 h, which is consistent with previous accounts (39,41,55). PMVECs rounded and lost cell adhesions, leaving only membranous strands as a means of cell-cell communication.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2A). Endothelial cell gaps visible by light microscopy were first noted after 3 h, which is consistent with previous accounts (39,41,55). PMVECs rounded and lost cell adhesions, leaving only membranous strands as a means of cell-cell communication.…”
Section: Resultssupporting
confidence: 90%
“…Our previous studies addressed ExoY's mechanism of action in the endothelium and the pulmonary microvasculature (5,41,55). Our laboratory and others have determined that ExoY is a purine and pyrimidine cyclase that synthesizes cytosolic cAMP, cGMP, and cUMP (39,41,59,72). The cAMP signal, in particular, results in endothelial cell tau hyperphosphorylation and insolubility, which result in dissociation of tau from microtubules, leading to their breakdown (5,46,55).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies further supported the notion that ExoY is a promiscuous cyclase, the cell type (s) responsible for increased cyclic nucleotide monophosphates were unclear; it was suggested that both epithelial and endothelial cells contribute to this increase in cyclic nucleotide monophosphates. We examined whether ExoY + produces both purine and pyrimidine cyclic nucleotide monophosphates in lung endothelium (Morrow et al 2015). Intoxication of pulmonary endothelium at an MOI of 20:1 with ExoY + produces cGMP first, followed by cUMP, and then cAMP; cCMP concentrations increase last, and this increase is of a relatively low magnitude.…”
Section: Exoy As a Purine And Pyrimidine Cyclasementioning
confidence: 99%
“…1b). We have seen that ExoY functions not only as an adenylyl cyclase, but rather, as a promiscuous purine and pyrimidine nucleotidyl cyclase in vascular endothelium, generating cGMP, cAMP, cUMP and, to a lesser extent, cCMP (Morrow et al 2015). The elevation of these cyclic nucleotide monophosphates causes endothelial tau hyperphosphorylation, which leads to microtubule breakdown and endothelial hyperpermeability (Balczon et al 2013; Morrow et al 2016; Ochoa et al 2012; Prasain et al 2009; Sayner et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, MRPs may help to detoxify cells with pathologically high cCMP or cUMP concentrations, e.g., after infection with ExoY-positive P. aeruginosa bacteria. The exotoxin ExoY is a nucleotidylyl cyclase, which causes a dramatic increase in cUMP concentration in infected tissues Morrow et al 2015). To the best of our knowledge, at the moment nothing is known about cIMP transport by MRPs.…”
Section: Inactivation Of Cnmps By Outward Transportmentioning
confidence: 99%